Enhancing portfolio assessment: a study on the implementation & outcomes of a new evaluation method - Abdul Rahman, Maisarah; Mohd Basri, Mohd Rafaei; Rejab, Abdul Rahman; Abu Hassan, Fatin Zahida; Abdul Jalil, Nor Liza; Dahari, Farrahana (Centre for Foundation Studies, IIUM, 2024)
This study delves into the efficacy and outcomes of a restructured portfolio assessment approach within the Department of Architecture and Environmental Design, Centre for Foundation Studies, IIUM, prompted by insights gleaned from an audit exercise. Its primary aim is to offer comprehensive insights into the effectiveness, consistency, and alignment of the improved assessment method with the department's learning objectives, thereby contributing substantially to the ongoing initiatives aimed at continual improvement of the academic programme. The research objectives are multifaceted, encompassing the evaluation of effectiveness, assessment of grading consistency, measurement of satisfaction levels among both students and academic staff, and determination of the alignment between the assessment process and the intended learning outcomes. Key research inquiries revolve around grading consistency, levels of satisfaction, and the degree of alignment with learning objectives. Participants in this study comprise a representative sample of 187 students and academic staff directly engaged in the portfolio assessment process. Employing surveys equipped with 10-point linear scale questionnaires, data collection is meticulously orchestrated following a sufficient period of implementation. The subsequent data analysis entails a thorough examination involving descriptive statistics and reliability analysis. Initial findings collected from the study reveal an encouraging trend of positive feedback pertaining to the implementation of the new portfolio assessment process. Nonetheless, concurrent with this optimism, concerns have surfaced regarding the familiarity and comprehension of the new process among participants, thus indicating potential areas necessitating further refinement and enhancement. In summation, this study assumes a pivotal role as a foundational cornerstone in the broader landscape of refining assessment practices within the department. By elucidating the effectiveness of the new assessment method and pinpointing areas for improvement, it aspires to catalyse a trajectory towards augmenting student learning outcomes and fostering heightened levels of satisfaction among department members.